Analisa Metode ANP pada Pemilihan Alat Cukur Rambut - Ima Kurniawan; Ogi Wahyudi; Marini Marini; Agus Perdana Windarto (KLIK: Kajian Ilmiah Informatika dan Komputer, 2021)
Barbershop business is a service business that has very bright prospects, considering that this business is needed by everyone, from children, teenagers, adults, to the elderly. The development of this business is certainly influenced by the fact that human hair continues to grow every second. When it is long, the hair will be cut. And, not everyone can cut their hair neatly and nicely, so many people choose to entrust the job to a hairdresser. To run this business, there are many tools and equipment that must be prepared, one of which is a hair clipper. There are many factors to consider when choosing a hair clipper. Therefore, to overcome this problem, the purpose of this study is to determine the sub-criteria in the selection of hair clippers and to choose the right hair shaver. In this study, the method used is the Analytic Network Process (ANP) method. This ANP method is a development of the Analytic Hierarchy Process (AHP) method. This ANP method is able to accommodate linkages between criteria, sub-criteria or alternatives. From the research that has been done, there are 4 criteria and 8 sub-criteria and 7 alternative choices. Based on the results of data processing, the weights for the criteria are: Price (0.35), Machine Type (0.32), Material (0.13), Function (0.19). While the weights for the alternatives are as follows: Kemei KM-809A Electric Hair Clipper (0.0507), Mitsuyama MS-5022 Professional Trimmer (0.029), Wahl Cordless Magic Clip (0.026), Nova NHC 3788 Professional Rechargeable Trimmer (0.0178), Philips HC3426/ 15 Hair Clipper (0.0156), Harnic HCL-008 Magnetic Hair Clipper (0.0121), Small Mountain STM-A008 (0.0072)